Penyuluhan Manajemen Kesehatan, Reproduksi, Sanitasi Kandang, dan Pengobatan Massal Ternak Kambing - Muhammad Mirandy Pratama Sirat; Madi Hartono; Purnama Edy Santosa; Ratna Ermawati; Siswanto Siswanto; Fani Setiawan; I Kadek Dwi Agus Candra Wijaya; Sherlina Widya Rahma; Siti Tika Fatmawati (Institut Pertanian Bogor, 2021)
Province of Lampung has a strategic opportunity for the development of ruminants because of the availability of natural resources that support it. One type of ruminant livestock is goat. People's goat farming is now widespread but the conditions of maintenance management are not optimal. Constraints that are still often faced by goat farmers are in terms of lack of knowledge on handling reproductive disorders and livestock health, cage sanitation that is not in accordance with regional geographical conditions and the lack of assistance for livestock treatment obtained. The Community Service Team Scheme Beginner Lecturers of BLU University of Lampung 2020 through counseling related to health management, reproduction and pen sanitation as well as mass treatment of goats were aims to increase knowledge and how to raise conventional people's livestock to be science-based. The target of the activity was goat breeders in Kota Agung Village, South Sungkai District, North Lampung Regency. Methods of activity, namely 1) Extension of health management, reproduction, and sanitation for goat sheds; 2) Implementing a pen sanitation program with cleaning and disinfection of the pen; and 3) Health checks and mass treatment. Activity measurement parameters to determine the response of extension participants to the implementation of community service activities by comparing changes in values in the initial evaluation (pre-test) and the final evaluation (post-test). Service activities were 1) 31 goat farmers was attending the counseling; 2) Mass treatment activities were carried out on 232 goats; and 3) Pen sanitation activities were carried out at 31 goat pen with the results of the evaluation of activities, namely the level of breeders' knowledge on the goat health knowledge increased by 54.02%; the reproductive knowledge increased by 26.77%; and the pen sanitation knowledge increased by 52.33% after the activities were implemented. Conclusion of the overall activities had a very large positive impact on farmers.